The Development of Analog and Digital Trainer Base on Arduino Uno in Microprocessor Programming Subjects - Sulistiyo, E; Meduri, NRH; Achmad, F; Wibawa, SC; Spoettï, G (IOP conference series. Materials Science and Engineering, 2021)
Based on observations in vocational schools, it was found that schools rarely had companion media in analog and digital learning, especially during the pandemic, students were not allowed to go to school. A media trainer is needed that can explain easily to students. The purpose of this research is to make analog and digital trainers based on Arduino Uno in microprocessor programming subjects, that are expected to solve these problems. The research method uses Research and Development (R&D) has 7 stages: (1) the potential and problem analysis stage, (2) the data collection stage, (3) the product design stage, (4) the product validation stage, (5) the product revision stage, (6) product trial phase, (7) data analysis and reporting stages. From the experimentation of making analog and digital trainers, the results obtained validation of the use of trainer assessment of 84.37%. It can be categorized as very valid as a companion media in learning. The validation of the use of job sheets is also categorized valid with a value of 81.6%. The overall results of students in responding to this trainer as a companion in learning were very good, 88.49%. So it can be concluded that an appropriate media can assist students in learning without the teacher, while based on validation and response states this media is valid and suitable to be used as a companion media in learning microprocessor programming. This trainer is recommended to be a learning medium for students with an explanation from the teacher to understand analog and digital material.